A genetic tool for evaluating male‐mediated stock introgression in Atlantic salmon. Issue 1 (10th January 2019) - Gabián, María; Morán, Paloma
Abstract: The Atlantic salmon shows strong population structure with reduced gene flow, owing to homing behaviour. Supportive breeding with allochtonous parr or fish‐farm escapees could affect native population genetic structure by the introgression of foreign genes. Mature male parr are potentially powerful vehicles for promoting introgression: they can fertilize eggs in competition with anadromous males. As a consequence, foreign males contribute more to introgression than foreign females. This effect must be taken into account for the correct development of conservation programmes. Foreign males constitute an inadvertent way to disrupt the genetic structure, as the allochtonous parr or fish‐farm escapees can survive in the river during the parr stage. A short polymorphic fragment of the sex‐determining gene ( sdY ) was used as a marker to assess introgression via males into south European salmon populations. In order to find haplotype variants for the intronic sequence of sdY, samples were investigated from 16 different rivers across the distribution range of the salmon, together with historical samples (1950–1960) from three Spanish rivers. Two novel haplotypes, in addition to the three already described in Atlantic salmon, were found for this locus. Most samples, including historical ones, displayed the common haplotype (D) previously found in salmon all over Europe; however, north European haplotype variants were also detected in salmon inhabiting the southern European rivers that were systematically supplemented with foreign stocks between 1981 and 1994. Analysis of haplotype variation in the sdY intron constitutes a powerful and inexpensive tool, not only to specifically assess male‐mediated introgression into natural populations of Atlantic salmon, but also for monitoring salmon escapees.